Ful-Ful Approach: Becoming a Mindful, Meaningful, and Joyful Learner Through Deep Learning - Hardika Saputra; Nur Aisyah Zainal (Innovate Inovation Teaching And Learning, 2026)
This research explores the concept of the Ful-Ful approach in deep learning, which integrates three key elements: Mindful Learning, Meaningful Learning, and Joyful Learning. The study aims to systematically review existing literature from the past five years to understand the contribution of these elements in enhancing deep learning processes. The Systematic Literature Review methodology is employed to identify, evaluate, and synthesize relevant studies. The findings highlight that Mindful Learning promotes focused attention and emotional regulation, while Meaningful Learning fosters deeper engagement by linking new knowledge to real-life contexts. Joyful Learning creates a positive and motivating learning environment that boosts intrinsic motivation. The integration of these three elements contributes significantly to a more effective and engaging learning experience. The research underscores the importance of incorporating these elements in educational practices to foster holistic and deep learning outcomes.